Wnt/β-catenin signalling: function, biological mechanisms, and therapeutic opportunities - Liu, Jiaqi; Xiao, Qing; Xiao, Jiani; Niu, Chenxi; Li, Yuanyuan; Zhang, Xiaojun; Zhou, Zhengwei; Shu, Guang; Yin, Gang (Signal transduction and targeted therapy, 2022)
The Wnt/β-catenin pathway comprises a family of proteins that play critical roles in embryonic development and adult tissue homeostasis. The deregulation of Wnt/β-catenin signalling often leads to various serious diseases, including cancer and non-cancer diseases. Although many articles have reviewed Wnt/β-catenin from various aspects, a systematic review encompassing the origin, composition, function, and clinical trials of the Wnt/β-catenin signalling pathway in tumour and diseases is lacking. In this article, we comprehensively review the Wnt/β-catenin pathway from the above five aspects in combination with the latest research. Finally, we propose challenges and opportunities for the development of small-molecular compounds targeting the Wnt signalling pathway in disease treatment.